2015
DOI: 10.1111/afe.12103
|View full text |Cite
|
Sign up to set email alerts
|

Response of walnut aphid populations to increasing foliar nitrogen content

Abstract: 1 An understanding of how fertilizer input affects pest populations and, consequently, the need for pesticide use would allow for the development of more effective integrated management strategies. 2 The present study addressed the response of walnut aphid Chromaphis juglandicola (Kaltenbach) (Hemiptera: Aphididae) populations to different levels of nitrogen application to walnut seedlings and the relationship between aphid density and chlorophyll content index (CCI), a non-invasive measure of foliar nitrogen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…Additional research is needed to confirm this assumption. Feeding by piercing-sucking herbivores is known to alter plant nutritional composition (e.g., Tobih et al 2002 , Xiao and Fadamiro 2010 , Cherry et al 2013 ), which in turn could affect the preference of these herbivores for host plants (e.g., Mace and Mills 2015 , Sétamou et al 2016 ). In the case of P. rubra , however, we found no evidence that feeding injury changes the composition of macro- (P, K, Ca, Mg, and S) or microelements (Mn, Zn, Fe, Cu, B, Na, and Al) in cranberry vines.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed to confirm this assumption. Feeding by piercing-sucking herbivores is known to alter plant nutritional composition (e.g., Tobih et al 2002 , Xiao and Fadamiro 2010 , Cherry et al 2013 ), which in turn could affect the preference of these herbivores for host plants (e.g., Mace and Mills 2015 , Sétamou et al 2016 ). In the case of P. rubra , however, we found no evidence that feeding injury changes the composition of macro- (P, K, Ca, Mg, and S) or microelements (Mn, Zn, Fe, Cu, B, Na, and Al) in cranberry vines.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen (N) is one of the main limiting factors for the optimal growth of insects. Rashid et al (2016) stated that excessive and/or inappropriate use of inorganic fertilizers can cause nutrient imbalances and lower pest resistance, via produce more broad, succulent and fresh leaves which could serve as suitable surfaces for egg-laying, increase herbivore's feeding preference, food consumption, survival, growth, reproduction, and population density and reflected for heavy crop damage by insects (Mace and Mills, 2015). Shalaby et al (2012) showed that infestation by P. mixta Vill., S. ocellatella Boyd.…”
Section: Introductionmentioning
confidence: 99%
“…), which may release herbivores from N limitation and possibly leads to outbreaks of herbivore populations, especially of insect species (Karowe and Martin , Ball et al. , Mace and Mills ). However, it is also possible that N addition may sometimes decrease plant tissue quality (Tao et al.…”
Section: Introductionmentioning
confidence: 99%